METODE PENELITIAN JURNALISTIK DAKWAH - Ramlah M (AL TAJDID, 2009)
The perspective of Moslems nowadays should be more criticsm towards the accepted daily information. One of challenges that should be coped by the muslims is to develop islamic jurnalism and to place value of Islam  as ideology of jurnalism in shake of Islam and muslim societyy. implemently islamic sociolize religious values of Islam and also reject and fitter the significant progress of any kind of ancient information from the western life. The existence of journalistic da’wah not only as a information tools of education and entertainment, but its main purpose is a religious leader as mission developing “Amar Ma’ruf Nahi Munkar”, in al-Qur’an S. Ali Imran (3): 104, Allah says : Some methods that can be ised in developing journalistic da’wah are as follows hipodermic needle research, uses and gratification, volume analysis and expression, and also framing  analysis.